A Study of Pulmonary Nodules from Multi-slice Computed Tomography Using 3-D Structure - Paing, May Phu; Choomchuay, Somsak (My University, 2018)
Multi-slice CT screening is an auspicious imaging test to detect the lung cancer. Formation of the pulmonary nodules in the lungs is the first suspicious sign of the lung cancer. The nodules appear as round or irregular shaped spots having size up to 30 mm on the CT scan. As the rate of cancer cases increases day by day, the manual detection of pulmonary nodules becomes a struggling way for the radiologists. The proposed method aims to develop an automated system to detect the pulmonary nodules using image processing techniques. Moreover, the needs of the conventional 2D detection are figured out and compensated by creating 3D structure.
Keywords: 3.0; lung cancer; multi-slice computed tomography (CT); pulmonary nodule